Artificial intelligence a modern approach - Russell, Stuart J.; Norvig, Peter (Pearson series in artificial intelligence, 2022)
The long-anticipated revision of "Artificial intelligence: a modern approach" explores the full breadth and depth of the field of artificial intelligence (AI). The 4th edition brings readers up to date on the latest technologies, presents concepts in a more unified manner, and offers new or expanded coverage of machine learning, deep learning, transfer learning, multi agent systems, robotics, natural language processing, causality, probabilistic programming, privacy, fairness, and safe AI.